Estimates of minimum energy requirements for range-controlled return of a nonlifting satellite from a circular orbit - Jackson, Charles M.; United States. National Aeronautics and Space Administration.; Langley Research Center. (Washington, [D.C.] : National Aeronautics and Space Administration, 1961)
Existing expressions are used to obtain the minimum propellant fraction required for return from a circular orbit as a function of vacuum trajectory range. The solutions for the parameters of the vacuum trajectory are matched to those of the atmospheric trajectory to obtain a complete return from orbit to earth. The results are restricted by the assumptions of (1) impulsive velocity change, (2) nearly circular transfer trajectory, (3) spherical earth, atmosphere, and gravitational field, (4) exponential atmospheric density variation with attitude and (5) a nonrotating atmosphere. Calculations are made to determine the effects of longitudinal and lateral range on required propellant fraction and reentry loading for a nonrotating earth and for several orbital altitudes. The single- and two-impulse method of return is made and the results indicate a "trade off" between propellant fraction required and landing-position accuracy. An example of a return mission from a polar orbit is discussed where the initial deorbit point is the intersection of the North Pole horizon with the satellite orbit. Some effects of a rotating earth are also considered. It is found that, for each target-orbital-plane longitudinal difference, there exists a target latitude for which the required propellant fraction is a minimum. Document ID: 20040006328. "NASA TN D-980." "Langley Research Center, Langley Air Force Base, Va." "November 1961." Cover title. Includes bibliographical references (p. 15). Existing expressions are used to obtain the minimum propellant fraction required for return from a circular orbit as a function of vacuum trajectory range. The solutions for the parameters of the vacuum trajectory are matched to those of the atmospheric trajectory to obtain a complete return from orbit to earth. The results are restricted by the assumptions of (1) impulsive velocity change, (2) nearly circular transfer trajectory, (3) spherical earth, atmosphere, and gravitational field, (4) exponential atmospheric density variation with attitude and (5) a nonrotating atmosphere. Calculations are made to determine the effects of longitudinal and lateral range on required propellant fraction and reentry loading for a nonrotating earth and for several orbital altitudes. The single- and two-impulse method of return is made and the results indicate a "trade off" between propellant fraction required and landing-position accuracy. An example of a return mission from a polar orbit is discussed where the initial deorbit point is the intersection of the North Pole horizon with the satellite orbit. Some effects of a rotating earth are also considered. It is found that, for each target-orbital-plane longitudinal difference, there exists a target latitude for which the required propellant fraction is a minimum. Mode of access: Internet.